Web Series Dokumenter Motorcycle Travelogue Episode "Kebun Teh Jogja Ki Suko” dengan Bentuk Laporan Perjalanan - Hakim, Latief Rakhman; Pungkiawan, Pius Rino (Rekam, 2024)
Documentary Web Series “Motorcycle Travelog Episode Kebun Teh Jogja Ki Suko” Documentary Web Series is a form of documentary that is broadcast periodically on a digital platform. Documentary web series "Motorcycle Travelogue" tells the story of a journey to a place that can be developed and has the potential to be better known to the public. This episode will focus on Ki Suko's tea plantation located in Nglinggo hamlet, Samigaluh, Kulon Progo. This plantation was started by a an ex-girlfriend named Sukohadi who chose to move back to his hometown to develop tea commodities, which was very suitable for the geographical conditions of his village which was at an altitude of 1000 meters above sea level with land conditions that were on the outskirts of the city. Pak Suko's tenacity produced very good results with the emergence of several variants, ranging from green tea, gold tea, yellow tea, and silver needles that reach millions of rupiah.The method of making documentary films uses the creative process method, namely Exploration, Improvisation/Experimentation and Formation or Embodiment of Works, The method is divided into pre-production, production and post-production stages. While the results of i Documentary film making will be opened using social media, namely through YouTube as a promotional medium. Key_word : Web Series, Documenter, Ki Suko tea plantation